P‐Doped SiOx/Si/SiOx Sandwich Anode for Li‐Ion Batteries to Achieve High Initial Coulombic Efficiency and Low Capacity Decay. Issue 3 (28th November 2021) - Im, Jinsol; Kwon, Jung‐Dae; Kim, Dong‐Ho; Yoon, Sukeun; Cho, Kuk Young
Abstract: Initial reversibility and excellent capacity retention are the key requirements for the success of high‐capacity electrode materials in high‐performance Li‐ion batteries and pose a number of challenges to development. Silicon has been regarded as a promising anode material because of its outstanding theoretical capacity. However, it suffers from colossal volume change and continuous formation of unstable solid electrolyte interphases during lithiation/delithiation processes, which eventually result in low initial Coulombic efficiency (ICE) and severe capacity decay. To circumvent these challenges, a new sandwich Si anode (SiO x /Si/SiO x ) free from prelithiation is designed and fabricated using a combination of P‐doping and SiO x layers. This new anode exhibits high conductivity and specific capacity compared to other Si thin‐film electrodes. Cells with SiO x /Si/SiO x anodes deliver the highest presently known ICE value among Si thin‐film anodes of 90.4% with a charge capacity of 3534 mA h g −1 . In addition, the SiO x layer has sufficient mechanical stability to accommodate the large volume change of the intervening Si layer during charge‐discharge cycling, exhibiting high potential for practical applications of Si thin‐film anodes. Abstract : The P‐doped silicon thin‐film supporting more electrical conducting SiO x layers are fabricated, and high‐performance lithium‐ion batteries (LIBs) are developed based on this anode. Attributed to the unique sandwich trilayer structure of the anode, these LIBs deliver high initial Coulombic efficiency, enhanced reversible capacity, low capacity decay, and prevent severe pulverization from volume change.